Changes in body water, lean body mass and body fat in persons with and without renal disfunction at several stages of chronic renal disease - Vilela Sangay, Ana Rosa (2020)
Objective: To study changes in body water, fat and lean body mass in healthy and sick persons (20-80 years of age) by glomerular filtration rate (GFR). Methods: A descriptive study was conducted among 198 subjects (healthy, with chronic renal disease without azotemia and with several stages of chronic renal disease by sex) using the following categories: Category 1 (GFR >140 ml/min/1.73 m2SC); Category 2 (GFR 90-140); Category 3 (GFR 60-89); Category 4 (GFR 30-59); Category 5 (GFR<30) and Category 6 (dialysis). Body weight, height, body water, body fat and lean body mass were measured using bioimpedance. Creatinine clearance (GFR), urea clearance, sodium and potassium were measured in 24-hour urine collection. ANOVA and eta square were used to contrast variables according to the proposed categories. GFR and lean body mass were correlated using bivariate regression and the rest of the variables with linear regression. Results: Relevant variables associated with loss of GFR were lean body mass and body water: ANOVA (p=0,000 for both) and eta square (0,178 y 0,165), respectively. Multivariate analysis only correlated GFR with age (r=-0,34; p=0,000) and lean body mass showed correlation with body water (r=0,861; p=0,000. Conclusions: Loss of GFR implies fundamentally loss of lean body mass and body water.